2014
DOI: 10.1002/jcb.24867
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine Stimulation of P2x7 Receptor by Atp Activates a Proliferative Pathway in Ovarian Carcinoma Cells

Abstract: P2X7 is a purinergic receptor-channel; its activation by ATP elicits a broad set of cellular actions, from apoptosis to signals for survival. Here, P2X7 expression and function was studied in human ovarian carcinoma (OCA) cells, and biopsies from non-cancerous and cancer patients were analyzed by immunohistochemistry. Ovarian surface epithelium in healthy tissue expressed P2X7 at a high level that was maintained throughout the cancer. The cell lines SKOV-3 and CAOV-3 were used to investigate P2X7 functions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 48 publications
(68 reference statements)
6
41
0
Order By: Relevance
“…These conclusions were supported by experiments with siRNA. Similar effect of P2X7R on cell survival and effects of the allosteric inhibition of P2X7R were also shown on mouse pancreatic stellate cells, 25 ovarian carcinoma cells 38 and in vivo on melanoma cancer model. 20 An important characteristic that makes PDAC aggressive is the ability of tumour cells to migrate and invade the surrounding or distant tissues.…”
Section: Discussionsupporting
confidence: 63%
“…These conclusions were supported by experiments with siRNA. Similar effect of P2X7R on cell survival and effects of the allosteric inhibition of P2X7R were also shown on mouse pancreatic stellate cells, 25 ovarian carcinoma cells 38 and in vivo on melanoma cancer model. 20 An important characteristic that makes PDAC aggressive is the ability of tumour cells to migrate and invade the surrounding or distant tissues.…”
Section: Discussionsupporting
confidence: 63%
“…We and others have shown that basal expression or low level stimulation of the P2×7R, as opposed to sustained pharmacological stimulation, drives cell growth, and accordingly P2×7R silencing or pharmacological blockade inhibits proliferation [15, 13, 26, 27]. Growth-stimulating effect of P2×7R is enhanced in low nutrient culture conditions [16, 17].…”
Section: Resultsmentioning
confidence: 99%
“…P2YRs have been traditionally credited with growth-promoting activity, as they are G- protein-coupled, and thus linked to phosphoinositide hydrolysis, Ca 2+ mobilization from intracellular stores and activation of the MAPK pathway. More recent studies showed that the P2×7R also supports cell proliferation [13, 26, 29]. This was unanticipated due to the well-known cytotoxic effect due to activation of the P2×7R-associated large conductance pore [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Tumors induced by the implant of HEK-293 cells heterologously expressing P2X7 receptors in immunodeficient mice showed elevated growth rate, an anaplastic phenotype, and high production of VEGF a well-known EMT inductor [67]. In cell lines derived from neuroblastoma or ovarian carcinoma, P2X7 receptor activity is correlated with high tumoral growth and metastatic induction, effects that involve PI3K/ AKT pathway activity [67][68][69][70]. Moreover, in pancreatic ductal adenocarcinoma cell lines, P2X7 receptor activity regulates migration and invasion, responses associated with EMT induction [71].…”
Section: Adora2amentioning
confidence: 99%